BAMBAREN VIGIL, Carlos. Consumo de alcohol y habla popular peruana, (Tesis doctoral, mimeografiada), Universidad Peruana Cayetano Heredia, Lima, 1973. - Cisneros, Luis Jaime (1972)
No contiene resumen